Finite Element Simulation for Dynamic Performance of a Dummy’s Head in Helicopter Anti-prang Tests - Lei Jingfa; Xuan Yan; Liu Tao; Zhang Miao; Sun Hong (MATEC Web of Conferences, 2018)
The dynamic performance of a dummy’s head plays a important role in the research of helicopter anti-prang testing. In this paper, we firstly construct the finite element model for a dummy’s head based on the parameter features of 50th percentile Chinese pilot. Then, the dynamic performance of the head model is simulated according to the calibration rules. After comparing the simulation results with the reference index of the dummy head’s dynamic performances, we find that the FE model has good anthropopathic integrality, and the simulation method used to analyze the dynamic performance of the dummy’s head is correct and validated. This paper has practical guiding significance in the study of helicopter anti-prang testing and other dummy parts, which also provide the reference value for the improvement of dummy structure.